Analysis of Factors Affecting Leprosy Cases in East Java Province with Spatial Autoregressive Model (SAR) - Desie Rahmawati; Hardian Bimanto (Jurnal Berkala Kesehatan, 2021)
Leprosy caused by Mycobacterium leprae is still a health problem in Indonesia. The incidence of leprosy in every regency/city in East Java Province indicates a spatial dependence. This study aims to describe the pattern of leprosy incidence and identify factors that influence the incidence of leprosy in East Java Province. This study used secondary data published by East Java Provincial Health Office and East Java Central Statistics Agency in 2018. The observation units in this study are 38 regencies/cities in East Java Province. The analytical method used is Spatial Autoregressive Model (SAR) which is a spatial approach based on area. Based on the results of analysis show that Moran's index value = 0.250 (p = 0.018) which means indicating a spatial dependency. The mean years' schools (p = 0.001) and the male population (p = 0.006) had a significant effect on the incidence of leprosy. Meanwhile, the percentage of healthy housing coverage (p = 0.111) and population density (p = 0.055) did not affect the incidence of leprosy. The spread pattern of leprosy in East Java Province is clustered in adjacent areas and factors that affect the incidence of leprosy are the mean years' schools and the male population.